2010
DOI: 10.1007/bf03217495
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen and its regioisomer, 3-acetamidophenol interfered with the growth ofEscherichia coli O157:H7

Abstract: Escherichia coli O157:H7 (O157) is an enterohemorrhagic pathogenic subtype, causing diarrhea and Hemolytic-uremic syndrome (HUS). Treatment for HUS patients might be accompanied with antibiotics and antispasmodics with analgesics for abdominal pain.Antiperistaltic effect of antispasmodics, however, may increase the risk of infection of O157 through the intestine. If analgesics also have antibacteiral effect, the prevention and cure of O157 could get benefits. Akhter, T. et al. (2010) reported the inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…If the TMB was washed off from O157 with PBS, followed by centrifugation, the O157 peroxidase reacted repeatly against TMB (data not shown), supporting the location of the peroxidase to be on membrane. In addition, the results from the peroxidase inhibitor, acetaminophen, from previous study also supported that the peroxidase activity was on the membrane, since the inhibitor could be easy washed off 18 . Cells, harvested after the addition of TMB or acetaminophen, were still viable.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…If the TMB was washed off from O157 with PBS, followed by centrifugation, the O157 peroxidase reacted repeatly against TMB (data not shown), supporting the location of the peroxidase to be on membrane. In addition, the results from the peroxidase inhibitor, acetaminophen, from previous study also supported that the peroxidase activity was on the membrane, since the inhibitor could be easy washed off 18 . Cells, harvested after the addition of TMB or acetaminophen, were still viable.…”
Section: Discussionmentioning
confidence: 59%
“…In the previous studies with bacterial peroxidase, horseradish peroxidase (HRP) in the medium proliferated growth of some lactic acid bacteria 17 . In addition, O157 growth was inhibited in the presence of acetaminophen and 3-acetamidophenol, where the mode of action was implicated with association of peroxidase inhibition 18 . However, the function of endogenous peroxidase was still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another study confirmed the anti-biofilm effect of ibuprofen against E. coli (Baldiris et al 2016). Controversy, the antimicrobial effect of 4-acetamidophenol against E. coli O157:H7 was reported (Kang and An 2010). Other studies affirmed the microbial degradation of 4-acetamidophenol when used as sole carbon and energy (Hu et al 2013;De Gusseme et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the voltammetric determination of acetaminophen in body fluids, the presence of concomitants such as uric acid (the primary product of purine metabolism) and ascorbic acid (widely found in association with various pharmacologically active substances including acetaminophen [27]) are considered a significant issue in the accuracy of the results because the oxidation peaks are overlapping on traditional electrodes. With regard to 3-acetamidophenol, it was included as an interferent due to its chemical similarity with acetaminophen -it is a nonhepatotoxic regioisomer of acetaminophen with analgesic properties [28].…”
Section: Introductionmentioning
confidence: 99%